Emerging risk in the construction industry: Recommendations for managing exposure to nanomaterials - Beatriz María Díaz-Soler; María Dolores Martínez-Aires; Mónica López-Alonso (Dyna, 2016)
Nanotechnology has aroused great interest in the construction industry because new materials with outstanding properties are being designed, and the features of traditional materials can be improved. However, exposure to nanomaterials is the most recent new emerging risk in the construction industry and the current knowledge about this topic is limited. This paper aims to identify the main aspects regarding the exposure to and use of nanomaterials in the construction sector from a risk prevention perspective. This starting point allows authors to establish a set of recommendations structured in order to identify how and where to act in order to manage the risk of exposure to nanomaterial on construction sites.